Strategi Diplomasi Publik Korea Selatan di Indonesia Melalui Korean Wave (2021-2022) - Tinangon, Jessica Nadyla Indriyani Novita; Hergianasari, Putri; Simanjuntak, Triesanto Romulo (Jurnal Ilmiah Widya Sosiopolitika; Vol 5 No 1 (2023): DIPLOMASI DAN ISU-ISU INTERNASIONAL, 2023)
South Korea's Public Diplomacy Strategy through the Korean Wave, has had an influence on Indonesia as one of the country's goals. The Korean Wave is one of the instruments or tools used by South Korea in the form of entertainment industry products such as music, drama and films that can introduce South Korea to the outside world, so that it is better known internationally. The method used by the author is descriptive qualitative, using the concept of Public Diplomacy using soft power techniques. This technique is an important tool in the implementation of Public Diplomacy. In this study, the author will discuss how the strategy used by South Korea to introduce the characteristics of the country and then make the Korean Wave so successful internationally, including Indonesia. The development of Korean music, drama and films in Indonesia is increasingly expanding with more and more fans every year. The results obtained are that the strategy used by South Korea involves various actors such as central ministries, local governments, and the private sector. South Korea established a five-year Public Diplomacy strategy and an annual Public Diplomacy implementation plan